2020
DOI: 10.3389/fphys.2020.570270
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Implications of CTRP3 in Obesity, Metabolic Dysfunction, and Cardiovascular Diseases: Potential of Therapeutic Interventions

Abstract: Adipose tissue, as the largest endocrine organ, secretes many biologically active molecules circulating in the bloodstream, collectively termed adipocytokines, which not only regulate the metabolism but also play a role in pathophysiological processes. C1q tumor necrosis factor (TNF)-related protein 3 (CTRP3) is a member of C1q tumor necrosis factor-related proteins (CTRPs), which is a paralog of adiponectin. CTRP3 has a wide range of effects on glucose/lipid metabolism, inflammation, and contributes to cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…As a novel metabolic regulator, CTRP3 has been detected in vascular endothelial cells and adventitial fibroblasts [14, 15] and is expressed predominantly in adipose tissue [21]. Previous studies have demonstrated that CTRP3 inhibits the activation of adventitial fibroblasts induced by TGFβ1 from the rat aorta in vitro [15] and improves vascular endothelial cells inflammation [14].…”
Section: Discussionmentioning
confidence: 99%
“…As a novel metabolic regulator, CTRP3 has been detected in vascular endothelial cells and adventitial fibroblasts [14, 15] and is expressed predominantly in adipose tissue [21]. Previous studies have demonstrated that CTRP3 inhibits the activation of adventitial fibroblasts induced by TGFβ1 from the rat aorta in vitro [15] and improves vascular endothelial cells inflammation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Acute MI is common in COVID-19 patients, and its incidence is proportional to disease severity. 14 , 15 , 16 , 17 Systemic inflammatory stress has been proposed as the major mechanism for MI. Injury is felt to represent a type II process with demand ischemia rather than inflammation leading to plaque destabilization and rupture.…”
Section: Presence Of Myocardial Injurymentioning
confidence: 99%
“…CTRP3, a well-studied member of CTRP family, was initially identified as a secretory protein expressed in the cartilage and kidney of adult mice (5). Notably, CTRP3 has been discovered to display abnormal expression in CVD (6). It has reported that CTRP3 protects mesenchymal stem cells from hypoxia and serum deprivation induced apoptosis through PI3K/Akt pathway (7).…”
Section: Introductionmentioning
confidence: 99%